HOTEL MARKETING INNOVATION STRATEGY IN TOURISM RECOVERY AFTER COVID 19 PANDEMIC - Kurnia Yusniar Rahman; Hamsu Hanafi; Sudarmi Sudarmi (JURNAL ILMU BUDAYA, 2022)
This research was conducted in three locations, namely hotels in Makassar, Bali, and Jakarta. This study aims to see the marketing innovation strategies carried out by the three hotels in tourism recovery after the Covid-19 pandemic. The research method used is the Mix method with SWOT analysis. Based on the results of the study, it was found that promotions carried out through advertisements in newspapers, magazines, the internet, radio, and environmental activities themselves were quite good. carry out various innovations in terms of management, especially in the field of computerization related to finance and also employees. In addition, the hotel also reduces the number of employees. Reduction of employee salaries, Implementation of the CHSE protocol, Promotion through the E-Commerce platform, Recruitment of employees carried out online, Use of daily labor, Making the hotel a stay facility for OTG, Providing training and self-development for Hotel HR, Afand fordable pricing.